2012
DOI: 10.1002/yea.2898
|View full text |Cite
|
Sign up to set email alerts
|

Genetic interactions of yeast NEP1 (EMG1), encoding an essential factor in ribosome biogenesis

Abstract: Nep1 methylates the hypermodified c1191 base of 18S rRNA and has an additional essential function during ribosome biogenesis. It is strongly conserved in eukaryotes and a point mutation causes the human Bowen-Conradi syndrome. To identify Δnep1-specific genetic interactions, viable deletions were screened genome-wide (SGA). Due to its essential function, we used, for the first time, query strain (Δnep1) with two additive suppressor conditions (mcRPS19B, nop6-1). Nep1 interacting genes correspond to ribosome bi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 72 publications
(87 reference statements)
2
17
0
Order By: Relevance
“…Consequently, we chose to mutate the equivalent residue and generated the substitution mutants, rrp8 – G209R and rrp8 – G209A . A serial dilution assay of the rrp8-ΔC mutant revealed the previously observed cold-sensitive phenotype and the hypersensitivity to paromomycin (28,29). The mutants expressing Rrp8–G209R and Rrp8–G209A also showed these phenotypes.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…Consequently, we chose to mutate the equivalent residue and generated the substitution mutants, rrp8 – G209R and rrp8 – G209A . A serial dilution assay of the rrp8-ΔC mutant revealed the previously observed cold-sensitive phenotype and the hypersensitivity to paromomycin (28,29). The mutants expressing Rrp8–G209R and Rrp8–G209A also showed these phenotypes.…”
Section: Resultsmentioning
confidence: 69%
“…The accumulation of an aberrant 21S rRNA in the Δ rrp8 deletion strain illustrated the role of Rrp8 in affecting rRNA processing at site A2 (28). In our previous study, we have also shown that Rrp8 plays a modest but yet significant role in 40S subunit biogenesis (29). Bioinformatics studies using distant homology detection and fold recognition predicted Rrp8 to be a class I MTase (Rossmann-like fold) with the MTase domain located in the C-terminal part of the protein (26).…”
Section: Resultsmentioning
confidence: 84%
See 2 more Smart Citations
“…Studies in yeast show that EMG1 genetically interacts with Utp30, another component of the SSU processome. This interaction supports incorporation of the ribosomal protein Rps19 into the assembling pre-ribosome [46]. In addition, overexpression of Rps19 rescues growth defects in EMG1 deficient yeast [47].…”
Section: Disease Of Emg1: Bowen-conradi Syndromementioning
confidence: 89%